Aplikasi Augmented Reality untuk Pembelajaran Organ Vital pada Tubuh Manusia Berbasis Android - Tesalonika Gracia Palilingan; Gladly C. Rorimpandey; Quido C. Kainde (JOINTER : Journal of Informatics Engineering, 2026)
This research aims to develop an Augmented Reality (AR) application based on Unity and Vuforia as a learning medium for human vital organs at SMP Negeri 1 Lembean Timur. In the context of education, which increasingly requires innovation, this AR application is expected to overcome the limitations of conventional learning methods that rely only on textbooks and 2D images. By utilizing AR technology, students can see three-dimensional (3D) models of vital organs in real-time, offering better details and more engaging interaction. The research results show that the implementation of the AR application has added a new, more interesting variation for students, making it easier for them to understand the shape, position, and function of vital organs. Additionally, this application provides an effective interactive learning alternative in the Natural Sciences (IPA) subject. Thus, the development of this AR application not only enhances students' understanding but also contributes to learning innovation at SMP Negeri 1 Lembean Timur.